2011
DOI: 10.1007/s10856-011-4330-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antimicrobial effect of Biosilicate® against anaerobic, microaerophilic and facultative anaerobic microorganisms

Abstract: This study assessed the antimicrobial activity of a new bioactive glass-ceramic (Biosilicate®) against anaerobic, microaerophilic, and facultative anaerobic microorganisms. Evaluation of the antimicrobial activity was carried out by three methods, namely agar diffusion, direct contact, and minimal inhibitory concentration (MIC). For the agar diffusion technique, bio glass-ceramic activity was observed against various microorganisms, with inhibition haloes ranging from 9.0 ± 1.0 to 22.3 ± 2.1 mm. For the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 32 publications
3
37
0
4
Order By: Relevance
“…In addition, recent data showed that BiosilicateÒ exhibits antimicrobial activity [32], a highly favorable characteristic when using it for maxillary reconstructions, due to the oral microbiota. Roriz et al [28] have investigated the use of this biomaterial for filling teeth sockets after dental extractions of dogs, finding adequate condition to install the endosseous implants after 12 weeks, and also after 8 weeks of implants installation, suggesting that the new vitroceramic can be indicated for this practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent data showed that BiosilicateÒ exhibits antimicrobial activity [32], a highly favorable characteristic when using it for maxillary reconstructions, due to the oral microbiota. Roriz et al [28] have investigated the use of this biomaterial for filling teeth sockets after dental extractions of dogs, finding adequate condition to install the endosseous implants after 12 weeks, and also after 8 weeks of implants installation, suggesting that the new vitroceramic can be indicated for this practice.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest rate of pH increase was recorded within the rst 4 h, and within 24 h a plateau (pH $ 9.0) was reached, which would be effective in inhibiting the growth of some bacteria. 8,9 However, the pH value in the Tris buffer, in which the pure polymer mats were immersed, showed a slight decrease ($7.05) within the initial two hours and then slightly increased to nearly 7.2. This is possibly attributed to the acetic acid residual, which has been used to dissolve chitosan.…”
Section: Inorganic Ion Release Analysismentioning
confidence: 99%
“…Recently, some studies have found that the local release of inorganic ions from bioactive glasses (BGs) can suppress microorganisms, stimulate collagen production, and accelerate the wound healing process. [7][8][9][10] It was found that BGs can be combined with so tissue and promote so tissue regeneration. 11 Moreover, BG can also reduce the inammatory response and wound exudate, and has a certain antibacterial and hemostatic potential, which has a positive therapeutic effect on the wound.…”
Section: Introductionmentioning
confidence: 99%
“…Often it is associated to a certain degree of cytotoxicity. However, several research works have proposed biocompatible glasses and glass ceramic with antibacterial properties910. It is critical to find a correct balance between bactericidal effects and biocompatibility properties.…”
mentioning
confidence: 99%